Psychometric testing of the Chinese version of Self‐Care of Coronary Heart Disease Inventory. Issue 2 (10th September 2020) - Chen, Zi; Chen, Yuan; Geng, Jing; Wang, Mian; Yu, Huidan
Abstract: Aim: To psychometrically test the Chinese version of Self‐Care of Coronary Heart Disease Inventory. Background: Self‐care is a significant step to impede the progression of coronary heart disease and serves as the primary outcome in self‐care interventions. In China, however, no instrument is available to measure self‐care in patients with coronary heart disease. To address this gap, we introduce the Self‐Care of Coronary Heart Disease Inventory into China. Design: A cross‐sectional design. Methods: We translated the inventory into Chinese using standardized methods. Then, it was psychometrically tested on a convenience sample of 301 patients with coronary heart disease (October 2017 to May 2018). Construct validity was evaluated via exploratory factor analysis and testing hypotheses. Internal consistency reliability was measured with Cronbach's alpha or composite reliability. Results: Both self‐care maintenance and management subscales showed a two‐factor structure, whereas self‐care confidence subscale showed a one‐dimension structure. All subscales were significantly correlated with associated variables (disease‐related knowledge and perceived control). The internal consistency reliability for all three subscales was acceptable. Conclusion: The Chinese version showed acceptable psychometric properties when applied to the sample group of this study. It is recommended for use in self‐care interventions targeting coronary heart disease. SUMMARY STATEMENT: What is already known about this topic? Self‐care is important for patients with coronary heart disease to control risk factors, reduce recurrence and improve the prognosis. Self‐Care of Coronary Heart Disease Inventory is developed based on the middle‐range theory of self‐care of chronic illnesses and shown acceptable psychometric properties. Self‐care of CHD is a growing focus of research and clinical practice; however, a tailored instrument to measure self‐care in Chinese patients with CHD is lacking. What this paper adds? This study provides the evidence of the construct validity and internal consistency reliability of the Chinese version of Self‐Care of Coronary Heart Disease Inventory. The Chinese version is a reliable and valid measure to assess the self‐care in patients with coronary heart disease. The implications of this paper: This study fills an important gap concerning measures of self‐care related to CHD in China. The Chinese version of Self‐Care of Coronary Heart Disease Inventory has the potential to be an ideal outcome measure in self‐care interventions and promote the research focusing on self‐care of CHD. This study adds the knowledge of the psychometric properties regarding the inventory in diverse cultural backgrounds.